2021
DOI: 10.3390/dj9020013
|View full text |Cite
|
Sign up to set email alerts
|

Direct versus Indirect Techniques to Menage Uncomplicated Crown Fractures of Anterior Teeth Following Dentoalveolar Trauma

Abstract: Dental trauma are the most common reasons for dental fractures in the anterior area, they have an incidence of 5% in the population, and in permanent teeth, they are mainly caused by sports. The most involved teeth are the maxillary anterior teeth. Direct composite restorations and indirect ceramic restorations are the therapy of choice for restoring anterior teeth after fracture when is not possible to reattach the tooth fragment. The treatment options in uncomplicated coronal fractures depend on various fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…9,10 The use and indications of laminate veneers have increased substantially in recent years including their use by athletes or sports practitioners. 8 Veneers are usually indicated to treat damaged teeth that have had previous trauma, teeth with uncomplicated crown fractures 11 or for aesthetic reasons. 12 A previous meta-analysis evaluated the main outcomes of glass-ceramic and feldspathic porcelain laminate veneers and reported that debonding occurred in 2% of the cases while fracture/chipping in 4%.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The use and indications of laminate veneers have increased substantially in recent years including their use by athletes or sports practitioners. 8 Veneers are usually indicated to treat damaged teeth that have had previous trauma, teeth with uncomplicated crown fractures 11 or for aesthetic reasons. 12 A previous meta-analysis evaluated the main outcomes of glass-ceramic and feldspathic porcelain laminate veneers and reported that debonding occurred in 2% of the cases while fracture/chipping in 4%.…”
Section: Introductionmentioning
confidence: 99%